Codon usage bias and its influencing factors for Y-linked genes in human. (August 2017) - Nath Choudhury, Monisha; Uddin, Arif; Chakraborty, Supriyo
Graphical abstract: Highlights: Analysis of codon usage pattern is important to understand the genetic and evolutionary characteristics of genomes. Codon bias index (CBI) and effective number of codons (ENC) indicated that the overall extent of codon usage bias was low in human Y-linked genes. The relative synonymous codon usage (RSCU) analysis suggested that CTG and AGA codons were over-represented in Y linked genes. The codon usage pattern was different in different Y linked genes as revealed from the correspondence analysis (COA). Abstract: The non-uniform usage of synonymous codons during translation of a protein is the codon usage bias and is mainly influenced by natural selection and mutation pressure. We have used bioinformatic approaches to analyze codon usage bias of human Y-linked genes. Effective number of codon (ENC) suggested that the overall extent of codon usage bias of genes was low. The relative synonymous codon usage (RSCU) analysis revealed that AGA and CTG codons were over-represented in Y-linked genes. Compositional constraint under mutation pressure influenced the codon usage pattern as revealed by the correspondence analysis (COA). Parity plot suggests that both natural selection and mutation pressure might have influenced the codon usage bias of Y-linked genes.